VILLAGE FUND MANAGEMENT: LESSON LEARNED FROM REGULATORY AN LEGITIMACY THEORY APPROACHESAT KENEP VILLAGE, BOJONEGORO, INDONESIA - Sholikha, Ririn Mushayadatus; Putra, Yuniarti Hidayah Suyoso (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
This study evaluates the implementation of village fund management based on the Minister of Home Affairs Regulation Number 20 of 2018 and the legitimacy theory. This qualitative research uses a case study approach to evaluate the application of village fund management starting from planning, implementation, administration, reporting, and accountability in Kenep village, Balen district, Bojonegoro. The results indicate there are some flaws in the implementation of village fund management in Kenep village. The time inaccuracy related to the procurement of goods and the realization process for the construction of infrastructure facilities which results in delays in infrastructure development, will also be a problem in reporting the realization of the use of village funds. Transparency must improve to avoid miscommunication with the community during the village fund management process. Active participation from the village government and society is essential in managing village funds to increase trust in the community, which confirms the legitimacy theory. This study is among the first to discuss village fund management from the legitimacy theory perspective.